Association between carnitine deficiency and the erythropoietin resistance index in patients undergoing peritoneal dialysis: a cross-sectional observational study. Issue 1 (1st January 2020) - Kaneko, Shohei; Hirai, Keiji; Morino, Junki; Minato, Saori; Yanai, Katsunori; Mutsuyoshi, Yuko; Ishii, Hiroki; Matsuyama, Momoko; Kitano, Taisuke; Shindo, Mitsutoshi; Aomatsu, Akinori; Miyazawa, Haruhisa; et al.
Abstract: Carnitine deficiency contributes to developing various pathological conditions, such as cardiac dysfunction, muscle weakness, and erythropoietin-resistant anemia in patients undergoing hemodialysis. However, a conclusion has not been reached concerning the prevalence and the effect of carnitine deficiency in patients undergoing peritoneal dialysis (PD). In this study, the prevalence of carnitine deficiency and the clinical factors associated with carnitine deficiency were investigated in 60 patients undergoing PD. The median age of the patients was 62.5 years (52.5–72.5 years), the proportion of male sex was 44/60 (73.3%), and the median PD period was 24 months (12–45 months). Carnitine deficiency (acyl carnitine/free carnitine ratio >0.4) was detected in 56/60 (93%) patients. Multiple regression analysis showed that the erythropoietin resistance index was independently associated with carnitine deficiency (β = 0.283, p  = 0.04). These results suggest that carnitine plays pivotal roles in hematogenesis in patients undergoing PD.